(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
According to the importance of studying total carbohydrates and its structure of monosaccharaides in the downstream applications for fermentation and food industry; this research was conducted to estimate the quantitative and qualitative content of carbohydrates in the microalgae Scenedesmus dimorphus isolated from local fresh water, and to determine the effects of the temperature (15, 25, 35°C) , the concentration of sodium nitrate (0.1, 0.25, 0.4 g / L) and the pH values ​​ (6, 7, 8) during growth. The results, showed that the total amount of carbohydrates ranged for all the different growth conditions between 14% and 44%, and galactose was prevalent among the monosaccharaides. It also showed that applied temperatures had no effect on the total carbohydrates, but the highest percentage of starch and cellulose was obtained at 25°C, and the lower temperature stimulated hemicellulose and glycoproteins formation. On the other hand, lower concentration of nitrate (0.1 g / L)produced the highest amount of carbohydrates and pectin in particular , while starch, cellulose and hemicellulose were not affected by nitrogen in the growth medium. The total carbohydrates, including the pectin, were increased by shifting the pH from the neutral value, while the cellulose and starch increased in the alkaline media only, on behalf of hemicellulose. اعتماداً على الحاجة لإيجاد مصادر جديدة غير تقليدية لكربوهيدرات ذات بنية هيكلية معينة لاستعمالها في التخمير والصناعات الغذائية، أُجري هذا البحث بهدف تقدير الكربوهيدرات الكلية ومحتواها من السكريات الأحادية في أحد أنواع الطحالب المعزول من المياه العذبة السورية Scenedesmus dimorphus، وتحديد مدى تَأثُّرها باختلاف درجة الحرارة (15، 25، 35 س°) وتركيز نترات الصوديوم (0.1، 0.25، 0.4 غ/ل) وقيم pH وسط النمو (6، 7، 8). تراوحت كمية الكربوهيدرات الكلية ضمن ظروف النمو المختلفة من 14% إلى 44%، وتميَّز الغالاكتوز بالسيادة على باقي أنواع السكريات الأحادية، وليس لتغير درجة الحرارة ضمن المجال 15-35 س° أي تأثير في كمية الكربوهيدرات الكلية، ولكن كانت أعلى نسبة من النشاء والسليلوز عند درجة الحرارة 25 س°، وقد حفزت الحرارة المنخفضة على تكوين الهِميسليلوز، والبروتينات السكرية. كما حقق التركيز المنخفض0.1غ/ل من نترات الصوديوم أكبر كمية من الكربوهيدرات بأعلى محتوى من البكتين، بينما لم يتأثر محتوى الكتلة الحيوية من النشا والسليلوز والهميسليلوز بنسبة النتروجين في وسط النمو، كما ازدادت النسبة الكلية للكربوهيدرات عند انزياح pH الوسط عن القيمة 7 ورافقها في ذلك زيادة البكتين، على عكس نسبة السليلوز والنشا التي ازدادت في الوسط القلوي على حساب الهميسليلوز.